Second Harmonic Generation from InGaAsP Waveguide at 1.3 gm Wavelength - Bierman, Robert Michael (My University, 1992)
Results of research on surface emission from a waveguide due to second-harmonic generation are presented. This concept has been applied and demonstrated here in the InP-InGaAsP material system for the first time, using a fundamental wavelength of 1.32 |im and a harmonic surface emission at 660 nm. The surface emission is the result of the nonlinear mixing of two counterpropagating modes in a waveguide. The theory of nonlinear optics that produces this effect is explained, leading up to a model that describes the behaviour of the surface emitting waveguide (SEWG). This model is then used to design a pseudo-optimized structure that was subsequently grown, characterized and tested. Device performance and behaviour are compared with theoretical predictions.
Keywords: second-harmonic generation; waveguide; surface emission